Ukuran Pemusatan Data - Siregar, Siti Aisyah; Zahrach, Eca May; Panggabean, Hadi Saputra (CV. Rayyan Dwi Bharata, 2025)
Calculating research results, especially in the social sciences, is not easy. This is because findings in the social sciences do not always show a direct impact on the treatment being studied, unlike other scientific research. For example, in studying the effect of experimental methods on student insight, a qualitative approach is often used to analyze the results. In this article, we provide an example of research that analyzes the mean, median, and mode values. The analysis was carried out manually by relying on the mathematical skills of experts. However, to obtain broader and more valid results in social science research, we recommend the use of computational software such as SPSS and Microsoft Excel. In conclusion, research in the social sciences has a higher level of complexity, and to process and draw conclusions from the data, researchers are advised to utilize various data analysis applications.